Zur Entwicklung des Lesens im Fremdsprachenunterricht - Sawicka, Maria (Studia Germanica Posnaniensia, 2018)
Reading, one of the four language skills developed in the process of foreign langua.ge instruction has a receptive character. However, it is more and more often interpreted not only in the categories of reception and production, but also as a kind of interaction, i.e. relations between the text (author) and the reader who co-creates the text. From this active role of the reader result certain consequences for foreign language teaching as far as the selection of texts and forms of working on them are concerned. When the texts a reselected it is important to take into account, apart from students' interests, their perceptive abilities in the linguistic and intellectual aspect, the structure of the text – from the point of view of form and content. These problems and examples of work with a literary and technical text are presented in this article.